Management of chronic urticaria in children: a clinical guideline - Carlo Caffarelli; Francesco Paravati; Maya El Hachem; Marzia Duse; Marcello Bergamini; Giovanni Simeone; Massimo Barbagallo; Roberto Bernardini; Paolo Bottau; Filomena Bugliaro; Silvia Caimmi; Fernanda Chiera; et al. (BMC, 2019)
Abstract The aim of this guidance is to provide recommendations to clinicians and other interested parties on chronic urticaria in children. The Italian Society for Pediatrics (SIP), the Italian Society for Allergy and Immunology (SIAIP), the Italian Society for Pediatric dermatology (SIDerP) convened a multidisciplinary panel that prepared clinical guidelines for diagnosis and management of chronic urticaria in childhood. Key questions on epidemiology, natural history, diagnosis, and management were developed. The literature was systematically searched and evaluated, recommendations were rated and algorithms for diagnosis and treatment were developed. The recommendations focus on identification of diseases and comorbidities, strategies to recognize triggering factors, improvement of treatment by individualized care.